Biological and Chemical Standardization of a Hop (Humulus lupulus) Botanical Dietary Supplement - Krause, Elizabeth (Biomed Chromatogr, 2014)
Concerned about the safety of conventional estrogen replacement therapy, women are using botanical dietary supplements as alternatives for the management of menopausal symptoms such as hot flashes. Before botanical dietary supplements can be evaluated clinically for safety and efficacy, botanically authenticated and standardized forms are required. To address the demand for a standardized, estrogenic botanical dietary supplement, an extract of hops (Humulus lupulus, L.) was developed. Although valued in the brewing of beer, hop extracts are used as anxiolytics and hypnotics and have well established estrogenic constituents. Starting with a hop cultivar used in the brewing industry, spent hops (the residue remaining after extraction of bitter acids) were formulated into a botanical dietary supplement that was then chemically and biologically standardized. Biological standardization utilized the estrogen dependent induction of alkaline phosphatase in the Ishikawa cell line. Chemical standardization was based on the prenylated phenols in hops that included estrogenic 8-prenylnaringenin (8-PN), its isomer 6-prenylnaringenin (6-PN), and pro-estrogenic isoxanthohumol (IX) and its isomeric chalcone xanthohumol (XN), all of which were measured using high performance liquid chromatography-tandem mass spectrometry (LC/MS-MS). The product of this process was a reproducible botanical extract suitable for subsequent investigations of safety and efficacy.